Communication Strategies Used during a Crisis in the Tourism and Hospitality Industry in Naivasha Sub-County - Muriuki, Robert; Inimah, Gertrude; Mwenda, Idah (International Journal of Communication and Public Relation, 2024)
Purpose: Since tourism is highly susceptible to shocks, and effects of crises in the industry can lead to several direct and indirect repercussions, appropriate communication techniques and strategies are needed to proactively overcome or prevent crises. However, in Kenya, assessment of the same is glaringly insufficient, hence, the need for the current study. The study objective was guided by a research question; What are the during-crisis communication strategies used in crises preparedness in the tourism and hospitality industry in Naivasha Sub-county? Methodology: The study was conducted among hotels in Naivasha Sub-County of Nakuru County of Kenya using a mixed research methodology. Using a sample of 362 employees through multi-stage and purposive sampling techniques, questionnaires were used to collect data among employees while 28 key informant interviews were used among the hotel managers. Descriptive and inferential statistics were used to analyze quantitative data. Findings: The study concluded that during crisis communication strategies featured issuance of accurate and consistent messages, giving precautions, dissemination of information on how to cope physically as well as information on prioritizing self-protection. The communication strategies during the crisis influenced the preparedness in small and insignificant amounts (sig. = .968). The results showed that communicating on precautions during a crisis was a special way and strategy to contain the effect of the crisis. The study found that more than half of the hotel staff 175(59.5%) agreed that their organizations give accurate and consistent messages on crisis preparedness. Unique Contribution to Theory, Practice and Policy: The study recommends that the Cabinet secretary in the Ministry of Tourism develop policies that spell and guide crisis management plans that acknowledge effective crisis communication strategies in hotels in the country. For individual hotel operators and managers in Naivasha subcounty, provision of regular information on crisis, and having a crisis communication plan in the precrisis stage will educate and sensitize the employees of the possible risks and how to handle them. This study findings will inform academia and be a base for scholars in mass communication in carrying out further studies in communicative strategies used in crises preparedness. The study findings inform development and roll out of policies that guide crisis management plans in tourism and hotel industry.